Healing of spongiosus-cutaneous fistula with Hyperbaric Oxygen Therapy (HBOT): a case report. Issue 1 (February 2018) - Della Camera, Pier A.; Cito, Gianmartin; Morselli, Simone; Sessa, Francesco; Facchiano, Davide; Cocci, Andrea; Gacci, Mauro; Serni, Sergio; Carini, Marco; Natali, Alessandro
Introduction: We present a case of a spongiosus-cutaneous fistula in a 39-year-old man with recurrent episodes of cutaneous abscess in dorsal middle third penis (5 × 3 cm) treated with Hyperbaric Oxygen Therapy (HBOT). Case report: After emptying nodular abscess, the patient was noncompliant for further surgery. Therefore, it was suggested the association between HBOT and antibiotic therapy. HBOT is carried out in a hyperbaric room, where the internal pressure is increased (compression phase) by entering compressed air up to 283.71 kPa in about 10 minutes. Every HBOT cycle lasted 24 days in which the patient had been taking Amoxicillin/Clavulanic Acid 875 mg/125 mg 3 tabs/day and Sulfamethoxazole/Trimethoprim 160 mg/800 mg 2 tabs/day for 2 weeks. At the end of the treatment, a penile magnetic resonance imaging and an ultrasonography were executed and they evidenced a complete remission of the lesion. In the subsequent 22 months, there was no recurrence. Conclusions: Our results suggest that HBOT is an effective treatment for chronic wounds, including a spongiosus-cutaneous fistula of unknown cause, when used in combination with conventional standard therapy or further interventions. At present time, the gold standard remains surgery; nevertheless, our experience with HBOT may stimulate its use in clinical trials.